2009
DOI: 10.1002/jcla.20295
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of metalloproteinases 2 and 9 and their inhibitors in physiologic and pre‐eclamptic pregnancy

Abstract: Matrix metalloproteinases (MMPs) are a family of zinc and calcium-dependent endopeptidases involved in remodeling and physiological homeostasis of extracellular matrix (ECM). The metalloproteinases activity is predominantly modulated by specific tissue inhibitors of matrix metalloproteinases (TIMPs). The balance between MMPs and TIMPs is likely to play an important role in remodeling uterine arteries in pregnancy, and it may represent means by which vasodilatation is maintained in later pregnancy. Moreover, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
120
4
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(140 citation statements)
references
References 20 publications
12
120
4
4
Order By: Relevance
“…While MMP-2 genotypes and haplotypes are not linked with hypertensive disorders of pregnancy, MMP-2 genotypes and haplotypes are associated with significant alterations in plasma MMP-2 and TIMP-2 concentrations in preeclampsia. The increased MMP-2 concentrations in preeclampsia agree with results previously reported (Montagnana et al, 2009;Myers et al, 2005b;Narumiya et al, 2001). Although the increased TIMP-2 concentrations that we found in preeclampsia contrast with previous results (Montagnana et al, 2009), our findings align with similar findings reported in another cross-sectional study (Tayebjee et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…While MMP-2 genotypes and haplotypes are not linked with hypertensive disorders of pregnancy, MMP-2 genotypes and haplotypes are associated with significant alterations in plasma MMP-2 and TIMP-2 concentrations in preeclampsia. The increased MMP-2 concentrations in preeclampsia agree with results previously reported (Montagnana et al, 2009;Myers et al, 2005b;Narumiya et al, 2001). Although the increased TIMP-2 concentrations that we found in preeclampsia contrast with previous results (Montagnana et al, 2009), our findings align with similar findings reported in another cross-sectional study (Tayebjee et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…The increased MMP-2 concentrations in preeclampsia agree with results previously reported (Montagnana et al, 2009;Myers et al, 2005b;Narumiya et al, 2001). Although the increased TIMP-2 concentrations that we found in preeclampsia contrast with previous results (Montagnana et al, 2009), our findings align with similar findings reported in another cross-sectional study (Tayebjee et al, 2005). It is possible that differences in the methods used to measure MMP-2 (ELISA vs. zymography), or differences between patients or gestational ages at sampling may explain the inconsistencies between studies (Montagnana et al, 2009; Myers et al, 2005b).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The balance between MMPs and TIMPs is likely to play an important role in the remodeling of uterine arteries in pregnancy, and it may represent the means by which vasodilatation is maintained in later pregnancy (12). It has been confirmed that MMP-2 and TIMP-1 expression is significantly increased in preeclampsic patients (13,14). Changes in circulating levels of MMP-9, TIMP-1 and TIMP-2 have also been noted in gestational hypertensive patients (15).…”
Section: Discussionmentioning
confidence: 92%
“…В плаценте представлено множество изоформ ММП. Большое внимание исследователей уделяется ММП 2-го и 9-го ти-пов, показана их роль при беременности: они определяют ход имплантации, плацентации, влияют на инвазивную способность трофобла-ста в эндометрии [9][10][11]. Относительно ММП-12 в литературе имеются единичные исследова-ния, посвященные изучению при беременно-сти [12][13][14].…”
Section: Introductionunclassified